Radiation robustness of normally-off GaN/HEMT power transistors (COTS). (September 2018) - Zerarka, M.; Crepel, O.
Abstract: This work aims to characterize the sensitivity to cosmic radiation of GaN Normally-off commercial technologies used in switching power conversion. It is necessary for the Space, Aeronautics and Automotive industries to characterize the radiation robustness of these new Commercial Off-The-Shelf (COTS) components in the operational and environmental conditions of their applications. Electrical behaviour of normally-off GaN power transistors under heavy ion test campaign is presented to define the cross section, determine the safe operating area (SOA) and analysis the mechanism of Single Event Effects (SEE) in these devices.